Soil nitrogen dynamics and spring wheat (Triticum aestivum) production in different cropping systems in the Swartland - Wessels, Pieter Gerhardus Wilhelmus (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--University of Stellenbosch, 2001.